SIMULASI LENSA GRATING TERHADAP EFISIENSI DIFRAKSI GRATING PADA SISTEM PEMISAH CAHAYA SPEKTRAL CONCENTRATED PHOTOVOLTAIC/THERMAL - Yuke Hary Laksono; Okasatria Novyanto (ROTOR, 2020)
A spectral beam splitting concentrated photovoltaic/thermal (SBS CPVT) system is a new technology in PV areas . In order to split the sunlight, the grating lens is used in this study. The tool of this study is G-Solver software which simulates the diffraction efficiency of visible light and infrared light of the blazed and binary grating lens. The aim of this paper is to analyze the potential of the diffraction efficiency of grating lens when applied in SBS CPVT. The result show that binary grating, the highest diffraction efficiency for the visible light is also almost unchanged for the aspect ratio from 1.4 to 2, but the peak wavelength shift from around 360 nm to 510 nm, while, for IR light, the diffraction efficiency decrease from aspect ratio 1.4 to 2. On the other hand, blazed grating, The highest diffraction efficiency for the visible light is almost unchanged for the aspect ratio from 1.4 to 2, but the peak wavelengths shift from around 350 nm to 500 nm. While IR light, the diffraction efficiency decrease with the aspect ratio 1.4 to 2